Semantic Mapping in Language Teaching in term of Memorizing Vocabularies - Wisran Wisran (P3I Luwu Raya, 2021)
When students learn English, they usually faced with many difficulties not only in specific language skills but also in vocabulary memorizing. Because of their learning habits and learning strategies, they failed to memorize words for a long time and to recall words when necessary. Based on literature review, it is found that semantic mapping has had good effects on vocabulary learning; especially it improves the retention and retrieval of word meanings.. The results indicated that the students in the experimental group outperformed those in the control condition in retaining word meanings. The results also proved that the students had positive attitudes towards semantic mapping. This leads to the implication that the semantic mapping can improve high school students’ vocabulary retention and is promising to vocabulary teaching and learning.